THE CORELATION BETWEEN BULLYING BEHAVIOR AND SELF-CONFIDENCE IN ADOLESCENTS AT JUNIOR HIGH SCHOOL 1 SIDOMULYO, SOUTH LAMPUNG REGENCY - Saputri, Diah Ayu; Agil, Hilda Meriyandah; Santosa, Puji Raharja (Jurnal Medicare, 2024)
This study discusses the problem of bullying in adolescents. This bullying has a negative impact that greatly affects a person's psychology, especially in terms of self-confidence. Confidence is an important thing, especially for adolescents in carrying out their developmental tasks, namely to find their identity and believe in the capacity of their abilities and believe in their own abilities. Factors that can affect self-confidence include family factors and environmental factors that plays a role in the formation of self-confidence in adolescents because at this time a child has grown cognitively and is able to choose and use his reasoning to accommodate what he thinks and wants. The research method used is quantitative with a cross-sectional approach and purposive sampling. The population in this study were 7th grade students at SMP Negeri 1 Sidomulyo, South Lampung Regency, amounting to 284 students. With the results of the study obtained P of (0.003), so the conclusion is that there is a relationship between bullying behavior and self-confidence in adolescents at SMP Negeri 1 Sidomulyo, South Lampung Regency.